Efektivitas Layanan Konseling Pastoral Online dalam Menangani Kecemasan dan Depresi pada Pemuda Gereja - Delvie Mangeghong; Julio Eleazer Nendissa (Journal Of Spirituality And Practical Theology, 2026)
This study examines the effectiveness of online pastoral counseling in addressing anxiety and depression among church youth within the context of digital life and contemporary psychosocial challenges. Online pastoral counseling is conceptualized as a contextual practice of pastoral theology that integrates Christian faith values with digital communication technologies. Using a qualitative descriptive approach, this study analyzes the experiences of church youth who participated in online pastoral counseling as well as the perspectives of pastoral counselors involved in the mentoring process. The findings indicate that online pastoral counseling contributes significantly to helping youth manage anxiety and depression through empathetic, reflective, and Christ-centered guidance. Key factors supporting its effectiveness include accessibility, a sense of psychological safety, and continuity of pastoral relationships. Furthermore, the study highlights the complementary role of digital pastoral practices and digital faith literacy as meaningful spaces for human–divine encounters. The study underscores the importance of pastoral ethics, counselor competence, and the integration of authentic spirituality to ensure that online pastoral counseling remains theologically sound and pastorally responsible.